Elizabeth's Bedfellows : An Intimate History of the Queen's Court - Whitelock, Anna (London Bloomsbury, 2013)
Elizabeth I acceded to the throne in 1558, restoring the Protestant faith to England. At the heart of the new queen's court lay Elizabeth's bedchamber, closely guarded by the favored women who helped her dress, looked after her jewels and shared her bed. This revealing history of the politics of intimacy uncovers the feminized world of the Elizabethan court.
Include Illustrations, Notes, Bibliography and Index.
An Intimate History of the Queen's Court.
Keywords: Queens--Social conditions -- Great Britain -- England -- Ladies-in-waiting